GIS-material for the archaeological project: Settlement location north of Kåtebosjön - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
The Swedish Rail Administration are planning for a parallel track along Stångåbanan railway, through Galtebo and Kåtebo among others, just south of Brokind in Vårdsberg parish, Linköping municipality. The Swedish National Heritage Board's contract archaeology division, UV Öst, has previously performed a survey, showing the existence of settlement remains within a limited area on a section of higher ground, consisting of a series of terraces, above lake Kåtebosjön. After decision by the County Administrative Board, UV Öst performed a preliminary investigation. The investigation concluded that most of the area was much disturbed by modern activities. The terraces were to a high extent build up of modern deposits. Underneath these were found pits with blasted rock. In the undisturbed areas, numerous traces of burnt tree roots and modern pits were found. UV Öst concluded that further investigations were unnecessary, and the excavation was thus terminated.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine whether any archaeological remains were going to be affected by the earthworks and, if so, to delimit the remains, define their character and, if possible, date them.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Banverket planerade anläggande av parallellväg längs med Stångåbanan genom bland annat Galtebo och Kåtebo, strax söder om Brokind i Vårdsbergs socken, Linköpings kommun. Riksantikvarieämbetet UV Öst hade tidigare genomfört en arkeologisk utredning som kunde konstatera boplatslämningar inom ett begränsat område i anslutning till ett höjdparti med en serie avsatser ned mot Kåtebosjön. Efter beslut av Länsstyrelsen i Östergötland genomförde därför UV Öst en arkeologisk förundersökning. Det kunde konstateras att större delen av området var kraftigt stört av yngre aktiviteter. Stora delar av terrasserna bedömdes utgöras av påförda massor. Under dessa påträffades ett flertal gropar med sprängsten, sannolikt bortsprängda block. Där orörd undergrund kunde hittas fanns rikligt med spår efter rotbränder och yngre gropar. UV Öst gjorde bedömningen att ytterligare arkeologiska insatser var onödiga varför förundersökningen avbröts.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att avgöra om fasta fornlämningar berördes av markarbetena samt att i så fall avgränsa fornlämningen, definiera dess karaktär och om möjligt datering.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatsläge ovanför Kåtebosjön
Keywords: prehistoric time; förhistorisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive